Identifikasi beban kerja mental operator forklift PT. NDIS menggunakan metode NASA-Task Load Index - Yusuf, Rusli; Fais, Moh Ainul; Chusaini, Achmad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to evaluate the mental workload of forklift operators at PT. NDIS, using the NASA-Task Load Index (NASA-TLX) method. Data was collected through an online questionnaire, with results indicating a "high" level of mental workload. The study identifies workload factors such as mental, physical, temporal demands, performance, effort, frustration, and fatigue, exacerbated by high operational demands. This research contributes to designing work systems that consider safety and health factors. Moreover, it deepens the understanding of employees' psychological conditions, which supports efforts to enhance productivity.